The Effects of Opioids on HIV Neuropathogenesis - Murphy, Aniella; Barbaro, John; Martínez-Aguado, Pablo; Chilunda, Vanessa; Jaureguiberry-Bravo, Matias; Berman, Joan W. (Frontiers in Immunology, 2019)
HIV associated neurocognitive disorders (HAND) are a group of neurological deficits that affect approximately half of people living with HIV (PLWH) despite effective antiretroviral therapy (ART). There are currently no reliable molecular biomarkers or treatments for HAND. Given the national opioid epidemic, as well as illegal and prescription use of opioid drugs among PLWH, it is critical to characterize the molecular interactions between HIV and opioids in cells of the CNS. It is also important to study the role of opioid substitution therapies in the context of HIV and CNS damage in vitro and in vivo. A major mechanism contributing to HIV neuropathogenesis is chronic, low-level inflammation in the CNS. HIV enters the brain within 4–8 days after peripheral infection and establishes CNS reservoirs, even in the context of ART, that are difficult to identify and eliminate. Infected cells, including monocytes, macrophages, and microglia, produce chemokines, cytokines, neurotoxic mediators, and viral proteins that contribute to chronic inflammation and ongoing neuronal damage. Opioids have been shown to impact these immune cells through a variety of molecular mechanisms, including opioid receptor binding and cross desensitization with chemokine receptors. The effects of opioid use on cognitive outcomes in individuals with HAND in clinical studies is variable, and thus multiple biological mechanisms are likely to contribute to the complex relationship between opioids and HIV in the CNS. In this review, we will examine what is known about both HIV and opioid mediated neuropathogenesis, and discuss key molecular processes that may be impacted by HIV and opioids in the context of neuroinflammation and CNS damage. We will also assess what is known about the effects of ART on these processes, and highlight areas of study that should be addressed in the context of ART.